2022
DOI: 10.1007/s00432-022-04072-4
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of PSMD14 in head and neck squamous cell carcinoma

Abstract: Purpose PSMD14 is an essential protein for proteasomal degradation. Inhibition of this protein disrupts homeostasis and inhibits cancer cell viability. Overexpression of PSMD14 was associated with advanced cancer characteristics and a worse prognosis in various carcinomas. This study aimed to analyze PSMD14 copy number variation, mRNA and protein expression in HNSCC, and its role as an independent prognostic biomarker. Methods PSMD14 mRNA expression and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…MMP2 can also promote lymphangiogenesis and lymph node metastasis (32,33). VEGF can induce lymphangiogenesis and promote lymph node metastasis (34,35). Our study showed that in human lung adenocarcinoma, the expression of USP4 was positively correlated with the expression of VEGF and MMP2, and the probability of lymph node metastasis was higher in lung adenocarcinoma patients with high…”
Section: Discussionmentioning
confidence: 69%
“…MMP2 can also promote lymphangiogenesis and lymph node metastasis (32,33). VEGF can induce lymphangiogenesis and promote lymph node metastasis (34,35). Our study showed that in human lung adenocarcinoma, the expression of USP4 was positively correlated with the expression of VEGF and MMP2, and the probability of lymph node metastasis was higher in lung adenocarcinoma patients with high…”
Section: Discussionmentioning
confidence: 69%
“…Among 17 upregulated DAPs, the FC values of Psmd14 and alpha-Crystallin B chain (Cryab) were high. Psmd14, an important component of the 26S proteasome, could remove misfolded or damaged proteins to maintain protein homeostasis, 28 and Cryab acts as a chaperone to prevent protein aggregation under stress conditions. 29 The increase of Psmd14 and Cryab in the H-YPLP group indicated that YPLP was beneficial to maintain muscle protein homeostasis and then improve muscle function.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Patient data were drawn from cBioportal.org “The Cancer Genome Atlas (TCGA), Firehose Legacy” and supplemented with “TCGA, PanCancer Atlas” (Liu et al 2018 ) and “TCGA, Nature 2015” (Lawrence et al 2015 ) as described before by Schnoell et al ( 2022 ). We included a total of 510 patients, who were treated between 1978 and 2012.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was done following the manufacturer's protocol of the Ultra Vision Quanto Detection System HRP (Thermo Fisher Scientific, Waltham, MA, USA) with the following modifications (Schnoell et al 2022 ). Briefly, samples were deparaffinized, rehydrated and incubated in H 2 O 2 to suppress endogenous peroxidase activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation